Liquid-phase oxidation of betulin over supported Ag NPs catalysts: Kinetic regularities, catalyst deactivation and reactivation; Molecular Catalysis; Vol. 528 - Grigorjeva (Grigoreva) A. R. Anna Romanovna; Kolobova E. N. Ekaterina Nikolaevna; Pakrieva E. G. Ekaterina Germanovna; Maki-Arvela P.; Kuznetsova S. N. Svetlana Nikolaevna; Carabineiro S. A. K. Sonia Alexandra Correia; Bogdanchikova N. Nina; Pestryakov A. N. Aleksey Nikolaevich; Murzin D. Yu. Dmitry Yurjevich (2022, 2022)
Title screen